A quasi-experimental design to assess the innovative impact of public procurement: An application to the Italian space industry. (March 2023) - Castelnovo, Paolo; Clò, Stefano; Florio, Massimo
Abstract: A growing number of empirical studies have shown that public procurement can be a relevant demand-side innovation policy. We assess the impact of public procurement on firms' innovation in the space industry. This is an important field of application because it widely uses public procurement and the procuring space agencies have distinctive characteristics, namely innovation-oriented mandate, relevant internal competences and professional skills. Specifically, we focus on the procurement activity of the Italian Space Agency over a 15-years period. We assess the causal impact of public procurement on suppliers' patenting activity by implementing a novel quasi-experimental design. Our approach allows addressing the endogeneity issues and potential estimation biases stemming from both the procurement selection process and its time heterogeneity. By combining matching techniques with a staggered diff-in-diff approach, we find that, after the beginning of the procurement collaboration, the supplier firms have increased on average their patent applications by roughly 10% compared to the control group. Such effect is increasing in time and persists for several years after the beginning of the procurement relationship. Highlights: We study the impact of the public procurement placed by a space agency on suppliers' innovation. The analysis is carried out on a sample of 461 firms providing high-tech products over the period 2003–2018. We develop a quasi-experimental strategy to address the endogeneity of the procurement selection process. After the procurement, suppliers increase on average their patent applications by 10% compared to the control group. Such effect persists for several years after the beginning of the procurement relationship and increases over time.